Optical studies of cadmium telluride quantum dots grown in glass - Allahverdi, C.; Yuekselici, M. H. (AMER INST PHYSICS, 2007)
CdTe quantum dots embedded in borosilicate matrix are produced by two-step heat treatment. The quantum confinement effect is observed in their optical absorption spectra. In the framework of effective mass approximation (EMA), the radius dependent oscillator strengths of the first eight allowed optical transitions (1s(h)-1s(e), 1p(h)-1p(e), 1d(h)-1d(e) etc.) are found for spherical semiconductor quantum dots which are in the strong confinement limit. These oscillator strengths are employed in an optical absorption model based on density-matrix approach. Thus, oscillator strength radius dependency is taken into account for small quantum dots in the strong confinement limit in the model. The average dot radius, its standard deviation and the number of dots in glass are determined with the help of this model from the optical absorption spectra.
Keywords: quantum dots; nanocrystallites; CdTe; oscillator strength; optical absorption; SEMICONDUCTOR MICROCRYSTALS; Physics